2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25942
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of Spatial Ability Improvement within an Engineering Mechanics Course: Statics

Abstract: Spatial ability has been an area of research for decades. Distinct correlations have been discovered regarding research into spatial ability and Science, Technology, Engineering, and Mathematics disciplines (STEM). However, spatial ability is a term that can be confusing to practitioners. For this purpose, spatial ability, a measure of an individual's capability to exercise a specific construct of spatial thinking, will be defined explicitly in this paper. Spatial ability has been positively correlated to succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…For the Statics problem-set, the average performance was 66%. MCT and PSVT:R correct responses paralleled previous findings reported by Wood et al, [27].…”
Section: Student Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…For the Statics problem-set, the average performance was 66%. MCT and PSVT:R correct responses paralleled previous findings reported by Wood et al, [27].…”
Section: Student Performancesupporting
confidence: 89%
“…PSVT:R problems require a student to mentally rotate an object represented with a 2-D drawing and to then select the proper solution orientation for that object [26]. These spatial problems were chosen due to their capability to represent two fundamental components of force addition, direction and magnitude, that are proposed to correlate with orientation (rotation) and proportion and that are represented with vector mathematics in a Statics course [27]. The Statics problem-set represents a traditional introductory Statics problem where a student must identify the resultant force consequential to two or three component forces.…”
Section: Engineering Problem-setsmentioning
confidence: 99%
“…Participants were recruited from an Engineering Statics class and an Anatomy class, just as in work by Wood, Goodridge, Call, & Sweeten 6 . Previous investigations with the Statics class had revealed that scores for engineering students were quite high on the PSVT:R and MCT.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed some research indicates their potential as more substantive than SAT math and verbal scores 4,5 . Current work is now just beginning to investigate why and where spatial ability is so important within engineering curricula 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Changing sometimes that environment from a traditional classroom to a metal workshop, collaborative spaces give students tools that will help them in the real world [3], and changing books for didactic models helps meet more diverse students' needs, as a variety in tasks is recommended to address the different learning styles [4]. Using physical materials in a learning task might change the nature of the knowledge gained, also stimulates the students' multiple senses and thus provides a more complete view increase students' interest in learning" [5] [6]. All the previous enhances student behavior and achievement, since it depends on how the student makes use of his/her environmental resources, and makes teachers more satisfied with their job.…”
Section: Introductionmentioning
confidence: 99%